New species of Delicata (Molineidae: Anoplostrongylinae) parasite of Cabassous tatouay (Desmarest, 1804) from the Atlantic Forest, Rio de Janeiro, Brazil - de Oliveira Simões, Raquel; de Andrade Silva, Beatriz Elise; Olifiers, Natalie; Bueno, Cecília; Maldonado Júnior, Arnaldo (Frontiers in Veterinary Science, 2024)
tatouay (Desmarest, 1804) from the Atlantic Forest, Rio de Janeiro, Brazil Dear editor Thank you for giving us the opportunity to submit a revised draft of the manuscript "New species of Delicata (Molineidae: Anaplostrongylinae) parasite of Cabassous tatouay (Desmarest, 1804) from the Atlantic Forest, Rio de Janeiro, Brazil" for publication in the Frontiers in Veterinary Science. We appreciate the time and effort that you and the reviewers dedicated to providing feedback on our manuscript. We have incorporated most of the suggestions made by the reviewers.Thank you for your attention.